Asset Management Security System Using RFID Technology - Rakshit, Soumyasanta; S. S. Sridhar, Dr. (International Journal of Engineering and Technology, 2018)
Using radio wave or radio frequency scanners to identify wirelessly any object is not so much complex in reality. The latest version of this technology is known as radio frequency identification or RFID. RFID has three building blocks: small tags built around microchips that carry a digital identification code; The RFID scanners also known as readers, the readers are also known as interrogators and networking hardware and the software to link scanners to the main computer databases that can be in hardware or cloud storage. In this project, we describe the implementation of RFID technology in the platform of asset management system in an organization. Using RFID technology track the all of the assets is the main aim of the project. The RFID interrogators open a serial port and then reads a RFID tag to use it as a unique parameter in the database to access and show the record associated to the RFID chip. Any change is wirelessly synchronized to the main database server.An admin will look after the whole server as an administration. If any new asset is introduced which is not in the main database, when the RFID scanner detects that the admin will get a notification message also in anyway if any asset will tamper by anything or anyone or if someone will try to steal any asset then again, the admin will get a notification message instantly.